Superheating field in superconductors with nanostructured surfaces - Pathirana, W. P. M. R.; Gurevich, A. (Frontiers in Electronic Materials, 2023)
We report calculations of a dc superheating field H sh in superconductors with nanostructured surfaces. Numerical simulations of the Ginzburg-Landau (GL) equations were performed for a superconductor with an inhomogeneous impurity concentration, a thin superconducting layer on top of another superconductor, and superconductor-insulator-superconductor (S-I-S) multilayers.The superheating field was calculated taking into account the instability of the Meissner state with a nonzero wavelength along the surface, which is essential for realistic values of the GL parameter κ. Simulations were done for the materials parameters of Nb and Nb 3 Sn at different values of κ and the mean free paths. We show that the impurity concentration profile at the surface and thicknesses of S-I-S multilayers can be optimized to enhance H sh above the bulk superheating fields of both Nb and Nb 3 Sn. For example, a S-I-S structure with 90 nm thick Nb 3 Sn layer on Nb can boost the superheating field up to ≈ 500 mT, while protecting the SRF cavity from dendritic thermomagnetic avalanches caused by local penetration of vortices.